A fragmentary-aspectual review of the 19th century scientists’ historical and linguistic views regarding the ideologeme of the Ukrainian language - Sokil, Bogdan (Theoria et Historia Scientiarum, 2023)
One of the urgent problems of modern diachronic sociolinguistics is fragmentarily outlined – an aspectual analysis of the views of the best representatives of the scientific and cultural community (Pavlo Biletskyi-Nosenko, Mykola Kostomarov, Ivan Kulzhynskyi, Amvrosii Metlynskyi, Oleksiy Pavlovskyi, Mykola Tsertelev) regarding the determination of the status of the Ukrainian language as an ideologeme represented in scientific discourse in Russian and Ukrainian timespace of the 19th century. Based on the identification of the main distinctive features of the Ukrainian language at all levels of the language system – phonetic, morpheme-word-forming, lexical, phraseological and grammatical, primarily morphological, characterized in the concepts of the mentioned scientists, it is shown that the Ukrainian language belongs to the original and ancient Slavic languages, which have their own independent path of development.